(untitled) (Third Sector Social Economic Review, 2023)
The aim of the study is to investigate which independent variable is effective in the selection of instruments traded in the debt securities market. As the data set, 303 debt instruments traded in the debt market and whose redemption date has not yet expired were used. The results obtained with multinomial logit and multinomial probit models are presented. While calculating the relative risk ratio, government bonds were determined as the basic election scenario. It has been determined that the clean price criterion is effective for investors to choose treasury bills instead. Closing, volume and simple weighted average criteria were effective in private sector bonds. Clean price, volume and cumulative volume were influential in the financing bills. When the values are examined in terms of closing prices, the risk is very high in the preference of financing bills and treasury bills. Looking at the marginal effects, it is seen that government and private sector bonds are preferred over the clean price. It was found that treasury and financing bills were preferred according to the closing price, and financing bills were preferred more. Government bonds and treasury bills stand out in terms of volume. All instruments except cumulative financial bonds are preferred. Only financial bonds are preferred at nominal value. In simple weighted average, government bonds and financing bills are preferred. In this way, it has been revealed that the investors prefer which vehicle according to which criteria over two models.